(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the composition and amount of flavonoids in the stock of Cistanche mongolica plant was studied for the first time by high-performance liquid chromatography method and the amount of flavonoids quercetin, apiginin, luteinin, rutin was determined and compared.